International stroke genetics consortium recommendations for studies of genetics of stroke outcome and recovery. Issue 3 (March 2022) - Lindgren, Arne G; Braun, Robynne G; Juhl Majersik, Jennifer; Clatworthy, Philip; Mainali, Shraddha; Derdeyn, Colin P; Maguire, Jane; Jern, Christina; Rosand, Jonathan; Cole, John W; Lee, Jin-Moo; Khatri, Pooja; et al.
Numerous biological mechanisms contribute to outcome after stroke, including brain injury, inflammation, and repair mechanisms. Clinical genetic studies have the potential to discover biological mechanisms affecting stroke recovery in humans and identify intervention targets. Large sample sizes are needed to detect commonly occurring genetic variations related to stroke brain injury and recovery. However, this usually requires combining data from multiple studies where consistent terminology, methodology, and data collection timelines are essential. Our group of expert stroke and rehabilitation clinicians and researchers with knowledge in genetics of stroke recovery here present recommendations for harmonizing phenotype data with focus on measures suitable for multicenter genetic studies of ischemic stroke brain injury and recovery. Our recommendations have been endorsed by the International Stroke Genetics Consortium.